Preparação, caracterização e testes de filmes bicamadas de polipirrol-poli(DMcT) sobre fibra de carbono para eletrodos de supercapacitores - Aikawa, Yves (Universidade Federal de São Carlos, 2013)
The aim of this work was to synthesize and characterize bilayered films of polypirrole and poly(2,5- dimercapto-1,3,4-thiadiazole) poly(DMcT) as possible materials for supercapacitor electrodes. Composites of carbon fiber (CF) and polypirrole (Ppy) were prepared at 0.8 V vs. SCE up to charges of 1, 2, 5 and 10 C in order to verify the experimental conditions to obtain films presenting the best morphological and electrochemical properties, as well as to optimize a methodology to obtain the composite CF/poly(DMcT)/Ppy. Morphological analyses indicated that Ppy is globular and grows homogeneously all over the CF surface, and electrochemical tests of the composites CF/Ppy led to the highest specific capacity for the thinnest (1 C) film. The presence of both polymeric films was confirmed by IR and Raman spectroscopies, and their distribution on the carbon fiber was checked by elemental analyses using Energy Dispersive X-Ray spectroscopy (EDS). Galvanostatic charge-discharge tests on a two-electrode cell having the same composite as cathode and anode (Type 1 supercapacitor) indicated a fair initial capacitance value of 200 F g-1 for the CF/Ppy (1 C) composite, but presenting low electrochemical stability (capacity loss of 72% after 1000 cycles). When narrower intervals for the cell voltage (0 to 0.5 V, 0 to 1 V and 0 to 2 V) were employed, both composites CF/Ppy and CF/poly(DMcT)/Ppy presented high electrochemical stability during 5000 cycles. Finally, spectroscopic studies indicated the reduced, polaronic and bipolaronic forms of Ppy, and possible interactions between the Ppy and poly(DMcT) molecules.
Preparation, characterization and tests of polypyrrole-poli(DMcT) bilayered films on carbon fiber as supercapacitor electrodes
Keywords: Eletroquímica; Energia; Polímeros condutores; CIENCIAS EXATAS E DA TERRA::QUIMICA